Combination of Murottal Surah Ar-Rahman and Lavender Aromatherapy on Dysmenorrhea Intesisity in Teenage Girls: Combination Of Murottal Surah Ar-Rahman And Lavender Aromatherapy - Sajodin; Aulia, Novita; Yuliani, Anita (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2025)
Adolescence is a transitional period from childhood to adulthood characterized by physical, emotional, and psychological changes. Adolescence, which is between the ages of 10-19 years, is a period in which the maturation of reproductive organs is often called puberty. During puberty, especially in adolescent girls, they will experience their first menstruation (menarche). Menstruation is a normal periodic uterine bleeding and is a physiological function that can occur in women. One of the disorders that women often experience during menstruation is dysmenorrhea. Dysmenorrhea is pain felt in the lower abdomen extending to the back due to uterine cramps and occurs before or during menstruation which causes activity disorders in women. The incidence of dysmenorrhea in Indonesia is still quite high. The combination of murottal surah ar-rahman & lavender aromatherapy is one of the non-pharmacological interventions to reduce the intensity of dysmenorrhea pain. The purpose of this study was to determine the effect of the combination of murottal surah ar-rahman & lavender aromatherapy on dysmenorrhea pain intensity in adolescent girls. This study is expected to add insight into the treatment of dysmenorrhea, especially complementary therapy in adolescent girls. This research design is quasi experiment with prepost- test design. The sample determination used the Federer formula, with a total sample of 36 respondents divided into 2 groups, namely 1 experimental group given an intervention for 30 minutes and 1 control group without intervention. The results of the paired t-test test in the experimental group obtained a p value = 0.001 (p value <0.05). The results of this study indicate the effect of a combination of murottal surah ar-rahman & lavender aromatherapy on dysmenorrhea pain intensity in adolescent girls. It is hoped that further research can develop non-pharmacological therapies, especially aromatherapy originating from Indonesia